2016
DOI: 10.1097/ccm.0000000000001817
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer Cell p38 Mitogen-Activated Protein Kinase Signaling Drives Postburn Hepatic Damage and Pulmonary Inflammation When Alcohol Intoxication Precedes Burn Injury

Abstract: Objective Clinical and animal studies demonstrate that alcohol intoxication at the time of injury worsens post-burn outcome. The purpose of this study was to determine the role and mechanism of Kupffer cell derangement in exacerbating post-burn end organ damage in alcohol exposed mice. Design Interventional study. Setting Research Institute. Subjects Male C57BL/6 mice. Interventions Alcohol administered 30 minutes before a 15% scald burn injury. Antecedent Kupffer cell depletion with clodronate liposom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…However, in several burn-models, additional alcohol administration has shown adverse effects. As such, increased neutrophil infiltration, edema formation in lung tissue, and potentiated LPS-induced activation of Kupffer cells was observed upon oral alcohol gavage and burn injury ( 42 , 43 ). Systemic and adipose tissue IL-6 levels were elevated in mice undergoing single binge alcohol exposure followed by burn, while even more pronounced cytokine response was induced by episodic alcohol exposure followed by burn ( 44 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, in several burn-models, additional alcohol administration has shown adverse effects. As such, increased neutrophil infiltration, edema formation in lung tissue, and potentiated LPS-induced activation of Kupffer cells was observed upon oral alcohol gavage and burn injury ( 42 , 43 ). Systemic and adipose tissue IL-6 levels were elevated in mice undergoing single binge alcohol exposure followed by burn, while even more pronounced cytokine response was induced by episodic alcohol exposure followed by burn ( 44 ).…”
Section: Discussionmentioning
confidence: 96%
“…Ethanol exposure also alters immune responses, such as decreasing NLRP3 activation and cytokine production (70)(71)(72). Taken together, alcohol exposure at the time of burn injury potentiates end-organ damage, including the lungs, liver, and gastrointestinal tract (73)(74)(75)(76)(77).…”
Section: Alcohol Usementioning
confidence: 99%
“…Two hit models have demonstrated that alcohol compounds injury [78,79]. In a model of diethyl–nitrosamine -induced hepatobiliary cancer, alcohol feeding increased serum ALT, liver inflammation, hepatobiliary cyst formation, proliferation (BrdU, p53 and cyclin D1), and upregulated cancer stem cell markers (nanog and CD133).…”
Section: The Role Of Hif-1α In Alcohol-mediated Liver Damagementioning
confidence: 99%